Examining Comprehension Strategy-Use Via Thinking Aloud and Comprehension Via Retelling: A Comparative Study of Proficient and Less Proficient ESL Readers at Matriculation Level - Ting, Su Hie (1995)
The aim of this study is to describe comprehension strategy-use and comprehension of ESL readers in the Science Matriculation Programme of Universiti Pertanian Malaysia. The nine proficient and eleven less proficient ESt readers of this study were selected based on their scores in a Test of Reading Skills. The use of comprehension strategies during reading was ecited via thinking - aloud procedures. The product of reading, comprehension, was assessed via oral retelling. The idea unit sin there telling protocols w ere compared with the content structure analysis of the think - aloud text to find out the percent age and kinds of idea units recalled. The think - aloud and retelling protocols were transcribed and analyzed.